Insights into youth nutritional status in Serbia: assessing prevalence and trend in the context of social determinants - Sanja Stanisavljević; Aleksandar Milovanović; Anđela Milovanović; Branko Jakovljević; Vesna Bjegović-Mikanović; Divna Kekuš (BMC Public Health)
Abstract Background The study aimed to assess the prevalence and distribution of different levels of nutritional status among young people, to examine its association with social determinants of health, and to analyse its trend over time. Method The research was a secondary analysis of the data from four national health surveys of the Serbian population. The research sample included 11,243 respondents, aged 15 to 29, both genders. A multivariate logistic regression model was applied to examine the association between socio-demographic characteristics, lifestyle, health status, and the level of respondents’ nutritional status. The trend analysis of the levels of nutritional status by the research years was done using multiple linear regression in adjusted models. Results A total of 63.3% of respondents had body mass index (BMI) in the normal weight range, 11.7% were underweight, 18.5% were pre-obese, and 6.2% were obese. The average BMI of the study participants was 23.01 ± 6.01. The female respondents were more frequently underweight, and the male respondents were pre-obese and obese. Different factors were associated with different nutritional status levels - for underweight: female gender (OR: 5.29), age 15–19 (OR: 0.06), being married/ in a relationship (OR: 0.69), living in Belgrade region (OR: 1.35), presence of chronic diseases (OR: 0.56), consumption of psychoactive substances (OR:0.56) and non-smoking (OR: 0.70); for pre-obesity: female gender (OR: 0.38), ages 15–19 (OR:0.36) and 20–24 (OR:0.65), being married/ in a relationship (OR: 1.39), having high wealth index (OR:1.30) and non-smoking status (OR:1.32); for obesity: female gender (OR: 0.36), ages 15–19 (OR:0.35) and 20–24 (OR:0.51), being married/ in a relationship (OR:2.31) and primary education level (OR:2.17). The trend analysis of nutritional status level in the research period showed an increase in the average value of the BMI of the respondents in the entire sample, as well as the prevalence of obesity, while the prevalence of underweight and pre-obesity decreased. Conclusion The research provided insight into the specific factors associated with and trends of levels of nutritional status of the young, leading to the conclusion that preventive and interventional public health programs and strategies must be fully adapted to their specific needs.